SCHEDULED COMMERCIAL BANKS IN INDIA - YAOUBA, Aoudou (IJRDO - Journal of Business Management, 2018)
The Indian financial system remains bank dominated, even as the availability of finance from alternative sources has increased in recent years. During 2016-17, bank credit accounted for 35 per cent of the total flow of financial resources to the commercial sector. The persistent deterioration in the banks asset quality has dented the profitability and constrained the financial intermediation. Consequent deleveraging has resulted in historically low credit growth, although subdued demand, especially from industry, has also restrained credit off-take. Demonetisation of specified bank notes (SBNs) in November 2016 impacted the banking sector’s performance transitorily in the form of a surge of low-cost deposits and abundance of liquidity in the system, which speeded up transmission of interest rate reduction and altered banks’ balance sheet structures even as they were engaged in managing the process of currency withdrawal and replacement.                                          The present study is on the deposit mobilization of scheduled Commercial Banks group wise in India taking into consideration the deposits, types of deposits, population wise deposits and credit limit.